Spectroscopy of 16B from quasi-free (p, pn) reaction with 17B. (December 2020) - Yang, Z. H.; Kubota, Y.; Corsi, A.; Authelet, G.; Baba, H.; Caesar, C.; Calvet, D.; Delbart, A.; Dozono, M.; Feng, J.; Flavigny, F.; Gheller, J.-M.; et al.
Abstract: Spectroscopy of 16 B plays an essential role in understanding the halo structure in 17 B, but very limited knowledge has so far been obtained. We have carried out a kinematically complete measurement on the spectroscopy of 16 B by using quasi-free (p, pn) reaction on 17 B. The level scheme of 16 B up to 5 MeV was made clear for the first time.